An Examination of Restorative Interventions and Racial Equity in Out-of-School Suspensions. Issue 2 (1st June 2018) - Gregory, Anne; Huang, Francis L.; Anyon, Yolanda; Greer, Eldridge; Downing, Barbara
Abstract: Districts have been engaged in efforts to reduce "differential processing" of discipline-referred students based on their racial backgrounds. They strive for fair assignment of exclusionary consequences across racial groups. The current study examines discipline records for one academic year in an urban school district ( N = 9, 039 discipline-referred students) to identify the factors associated with equitable assignment of out-of-school suspension (OSS). Multilevel logistic regression found that student participation in restorative interventions substantially reduced the odds that individual students received OSS. However, such participation was only marginally associated with more comparable assignment of OSS to Black students relative to their White peers. Together these findings suggest that alternatives to suspension, such as restorative interventions, may yield benefits for all student groups, but they may result in only marginal narrowing of the disparities in suspension rates between Black and White students. This indicates that greater attention is needed to address the inequitable school contexts in which disparities arise.